Neurorobotics—A Thriving Community and a Promising Pathway Toward Intelligent Cognitive Robots - Krichmar, Jeffrey L. (Frontiers in Neurorobotics, 2018)
Neurorobots are robots whose control has been modeled after some aspect of the brain (Krichmar and Wagatsuma, 2011). Since the brain is so closely coupled to the body and situated in the environment, Neurorobots can be a powerful tool for studying neural function in a holistic fashion. It may also be a means to develop autonomous systems that have some level of biological intelligence. The present article provides my perspective on this field, points out some of the landmark events, and discusses its future potential.